Activation of spo0A transcription by sigma H is necessary for sporulation but not for competence in Bacillus subtilis. - Siranosian, K J (1994)
spo0A and spo0H are needed for the initiation of sporulation and for the development of genetic competence in Bacillus subtilis. Transcription of spo0A initiates from two promoters, Pv and Ps. Pv is active during vegetative growth and is recognized by RNA polymerase containing sigma A. Expression from Ps increases during sporulation and depends on sigma H, the spo0H gene product. A deletion mutation, spo0A delta Ps, that removes the promoter controlled by sigma H blocked sporulation but had no detectable effect on competence. These results indicate that expression of spo0A from Ps is necessary for sporulation and that the requirement for spo0H in competence development is not due to its role in expression of spo0A.